Emergency Caller- An On-bed Patient Health Care in Hospitals - Kaur, Arshdeep; Baljit Kaur, Gill (International Journal of Computer Sciences and Engineering, 2025)
An important phase in the care and improvement of a patient’s health is performed by a caretaker. Thus the proposed work provides the prototype of an algorithm named Emergency Caller comprising of both hardware and software components both at patient and nurse ends. Here is a system implementing a clinical scenario where this electronic system will reduce the possibility of nurse ignorance and improve safety of the patient. The work is an early attempt to introduce effective care in clinical scenarios. Nurses are the main caring faculty in hospitals. This care is very important for the patient who cannot walk or stand for long time and mostly for the critical condition patient who can’t wait for a second. Care takers at hospitals are unable to take care of each and every patient simultaneously. To address this problem, given approach is used for patients. The patient will be provided with a remote having keys on it corresponding to particular tasks. This remote designed using AVR micro-controller and RF Module will transmit the instructions wirelessly to the PC of the ward incharge. The PC is connected with RF Receiver. Received information is streamed into a computer using software developed in MATLAB and the instructions get announced to the ward in charge automatically. The foremost objective of this project is to develop a system which reduces the cost of health care and ease the burden on the nurses thus providing better supervision of the patients as their call cannot be ignored thereafter. The prototype finds many applications in hospitals, nursing homes, rehabilitation centers and other health departments.